Playful method and mathematics through ITCs to practice entire numbers operations - Valdés Núñez, Juan Bautista (Universidad Pedagógica y Tecnológica de Colombia, 2011)
To make a diagnosis of the handling of integer numbers, flaws in the students of the institution was evident educational San Nicolas of the municipality of Tuta (Boyacá) in grades sixth to eighth, for this reason, considered implement recreational environments recreational mathematics with TIC’s sthrough the analysis, development and implementation of the MEC for the teaching of the basic operations with integers numbers, allowing more logical reasoning and the mental agility of the students. Implementing and developing the constructivist pedagogy, methodology of the classroom, learning by doing, learn playing and learn recreating, supported by the use of the developed MEC. The process of gathering information, was held with the objective to implement population, surveys, interviews, chats with students and evidence on the subject. Them a test was performed before and after the use of the MEC to the students themselves. To resolve the assumptions made is continued proof of ranges with sign of Wilcoxon. Students under investigation are going through the stages described by Piaget, the first stage of concrete operations and then those of formal operations.